Integrated STEAM Education for Students' Creativity Development - Josina Filipe; Mónica Baptista; Teresa Conceição (MDPI AG, 2024)
This study aims to explore how a learning sequence designed with an Integrated STEAM Education perspective (iSTEAM) contributes to students' levels of creativity. The participants in this study were students from 9th and 10th grade with ages between 14 and 16 years old. Students were challenged to produce a soundtrack for an animation video. This was achieved by building artifacts and using the phenomena of physics under study (mechanical energy) to produce sound effects. These were later digitally recorded and assembled to build the video's soundtrack. This research work contributes to addressing the importance of STEAM education integration and of digital competence in developing students' creativity in problem solving.